Knowledge and critical thinking skills increase clinical reasoning ability in urogenital disorders: a Universitas Sriwijaya Medical Faculty experience (Faculty of Medicine Universitas Indonesia, 2009)
Aim Clinical reasoning is one of the essential competencies for medical practitioners, so that it must be exercised by medical students. Studies on quantitative evidence of factors influencing clinical reasoning abilicy of students are limited. The aim of this study was to determine the influence of knowledge and other factors on the clinical reasoning abiliry ofthe students, which can serve as reference to establish methods for learning ctinical reasoning. Methods This is a cross-sectional study on fourth semester students enrolled in the Competency-based Curriculum of the Medical Faculty, University of Sriwijaya. Data on clinical reasoning abilily and risk factors during urogenital blockwere collected inApril 2008, when the students have just completed the btock. Clinical reasoning abiliry was tested using the Script Concordance test and the risk factors were evaluated based on formative tests, block summative assessments, and student characteristics. Data were analyzed by Cox regression. Results The prevalence of low clinical reasoning ability of the 132 students was 38.6%. The group with low basic knowledge was found to have 63% risk ol low clinical reasoning abiliry when compared to those with high basic knowledge (adjusted RR = 1.63; 95% conidence intewal (Ct): 1.10 -2.42). When compared to students with high critical thinking skitls, those with lory critical thinking skills had 2.3 time to be low clinical reasoning abitity (adjusted RR : 2.30; 95% CI: 1.55 - 3.41). Conclusion Students with low critical thinking skills or with inadequate knowledge had a higher risk of low clinical reasoning ability. (Med J Indones 2009; 18: 53-9) Keywords: clinical reasoning, basic knowledge, critical thinking, competency-based curriculum